The implementation of authentic language input in second language (L2) teaching: Pedagogical arguments - Maria Skiada (Peoples' Friendship University of Russia (RUDN University), 2021)
This paper was written at the same time that the annual language and culture seminar of Hellenic Culture School Switzerland was being held in Greece. That was a felicitous coincidence, since it allowed the observation and interpretation of the students' learning behaviour and their target language interactions within its native environment. This short immersion into authentic language and culture input was welcomed by students of all proficiency levels as a challenge and call for participating in a new, enriched learning activity performed within a natural, real-life situation and hence, a more purposeful and meaningful communication context. Students were led to a self-directed reception and assimilation of language input, applying their own strategies, experiences or intuition. This attitude of students, normally deprived of a native language environment, reflects the need to incorporate authentic materials in L2 classes based on their ability to function as substitutes for the native environment, which is missing, and on their potential to become vehicles for language progress, pragmatic and cultural awareness. The importance of authentic texts in language learning has been discussed by theorists in applied linguistics and language learning throughout the 20th century but with the development of the communicative approach and task-based learning it has become a leading feature of language teaching materials. This paper explores the development of task authenticity in the selection of language teaching materials in class and examines the arguments for their use, based on the analysis of culture, currency and challenge.